Faktor Penyebab Penumpukan Sampah Plastik Di Kota Merauke Dan Upaya Untuk Melestarikan Lingkungan Melalui Ensiklik Laudato Si - Subu, Yan Yusuf; Bala, Karolus B (Jurnal Masalah Pastoral, 2024)
The purpose of this study is to examine in depth and find evidence regarding the factors that cause the accumulation of plastic waste and how it affects the natural environment in the city of Merauke, South Papua. Primary data was obtained through field observations, in-depth interviews and documentation. Interviews were conducted with 15 informants directly in the field (Management of the Warrior Mandiri Waste Bank Group, Heads of RTs, Cleaners, Communities). A number of informants above were selected through purposive sampling techniques based on their mastery of the issues and information being studied. The results of data management, using a qualitative descriptive approach, show that there are 4 factors that are the main causes of the accumulation of plastic waste in the city of Merauke. First, technological development factors. Second, the education factor. Third, the factor of community behavior patterns. Fourth, the lack of good cooperation between the government and waste bank business groups and the community. The impacts that arise due to the accumulation of plastic waste are public health problems, environmental pollution (soil pollution, air pollution, water pollution, flooding). Efforts that can be made to overcome the problem of waste accumulation in Merauke city are to increase cooperation between the local government, the community (inviting people to become garbage customers in each RT) and waste bank groups, and increase residents' awareness not to litter. These efforts are one form of realization of the Laudato Si encyclical which encourages every member of the Church to be able to act concretely in dealing with the problem of waste.